Sanatçı Ve Artefakt Birliği: Sinemada Oyuncu Olmak - Saliji, Sali (The Turkish Online Journal of Design Art and Communication, 2016)
Acting is a very special and specific art form, be it in cinema or not it significantly differs from other art forms. First of all in the art of acting, created by the artist and thus the created work (artifact) represents a union. For example, a writer writes a novel, a composer composes music; painters do paintings, but only the actor is at the same time the creator and the result of his/hers own art. This feature of the actor not only determines the narrative expression it also determines the inner and private life of the actors. Though the existence of the actor is not a life, which is only consisted of his own, but also it is the life of others, there is a continuing public side in an actor’s life. Most of the actor’s lives are identified with the characters they play, and in certain cases the characters they play goes into a realm beyond the actors and take a shape a life form of its own in a sense it exchanges the place of the real character. Therefore, actors are inevitably forced to live a life of constant dilemma. Prior to anything else, it must be admitted that this is a psychological burden. This state of neither mind nor situation has to be considered by every director, and understood that to work with the actors is to work with a palette of rich hues, of emotionally high and low volumes and of highly sensitive and easily affected personas.
Keywords: Sinema; Kamera Önü Oyunculuk; Yönetmen; Oyuncu; Tiyatro; Seyirci; Cinema; Acting In Front Of The Camera; Film Director; Actor; Theater; Audience